Underwater Broadband Source Localization Based on Modal Filtering and Features Extraction. (26th April 2010) - Lopatka Lopatka, Maciej Maciej; Le Touzé Le Touzé, Grégoire Grégoire; Nicolas Nicolas, Barbara Barbara; Cristol Cristol, Xavier Xavier; Mars Mars, Jérôme I. Jérôme I.; Fattaccioli Fattaccioli, Dominique Dominique
Abstract : Passive source localization is a crucial issue in underwater acoustics. In this paper, we focus on shallow water environment (0 to 400 m) and broadband Ultra-Low Frequency acoustic sources (1 to 100 Hz). In this configuration and at a long range, the acoustic propagation can be described by normal mode theory. The propagating signal breaks up into a series of depth-dependent modes. These modes carry information about the source position. Mode excitation factors and mode phases analysis allow, respectively, localization in depth and distance. We propose two different approaches to achieve the localization: multidimensional approach (using a horizontal array of hydrophones) based on frequency-wavenumber transform (F - K method) and monodimensional approach (using a single hydrophone) based on adapted spectral representation (F T a method). For both approaches, we propose first complete tools for modal filtering, and then depth and distance estimators. We show that adding mode sign and source spectrum informations improves considerably the localization performance in depth. The reference acoustic field needed for depth localization is simulated with the new realistic propagation modelMoctesuma. The feasibility of both approaches, F - K and F T a, are validated on data simulated in shallow water for different configurations. The performance of localization, in depth and distance, is very satisfactory.